Factors influencing the efficiency of Malaysian local governments - Mohd Said, Julia; Mohd. Amin, Husniyati; Ismail, Suhaiza (Faculty of Business & Accountancy, University of Malaya, 2020)
Purposes – The aim of this paper is to investigate the factors influencing the efficiency of the Malaysian local governments. Three measures of efficiency are considered that are: (i) technical efficiency(TE), (ii) pure technical efficiency (PTE) and (iii) scale efficiency (SE). Design/methodology/approach – This study uses secondary data from annual financial statements of local governments in Malaysia. Financial statements from 2008 to 2015 from 35 local governments were obtained. Panel regression based on the ordinary least square was used to examine the determinants of efficiency of the Malaysian local governments. Findings – The results reveal that the population size and value of assets have positive and significant influence on the PTE, economic independence has positive and significant influence on the TE and SE, while the dependence on tax revenues is found negatively and significantly associated with all the three measures of efficiency (i.e. TE, PTE and SE). Originality/value – The paper provides empirical evidence on the determinants of efficiency of local governments in Malaysia. More importantly, the investigation on the factors was carried out for three measures of efficiency that are TE, PTE and SE.